Thiamine Alleviates High-Concentrate-Diet-Induced Oxidative Stress, Apoptosis, and Protects the Rumen Epithelial Barrier Function in Goats - Ma, Yi; Zhang, Ying; Elmhadi, Mawda; Zhang, Hao; Wang, Hongrong (Frontiers in Veterinary Science, 2021)
High-concentrate diets are continually used in ruminants to meet the needs of milk yield, which can lead to the occurrence of subacute rumen acidosis in ruminants. This study investigated the protective effects of dietary thiamine supplementation on the damage of the ruminal epithelium barrier function in goats fed a high-concentrate diet. Twenty-four healthy Boer goats (live weight of 35.62 ± 2.4 kg; age, 1 year) were randomly assigned into three treatments, with eight goats in each treatment, consuming one of three diets: a low-concentrate diet (CON; concentrate/forage, 30:70), a high-concentrate diet (HC; concentrate/forage, 70:30), or a high-concentrate diet with 200 mg of thiamine/kg of dry matter intake (HCT; concentrate/forage, 70:30) for 12 weeks. The additional dose of thiamine was based on our previous study wherein thiamine ameliorates inflammation. Compared with HC treatment, the HCT treatment had markedly higher concentrations of glutathione, superoxide dismutase, and glutathione peroxidase and total antioxidant capacity (P < 0.05) in plasma and rumen epithelium. The results showed that the apoptosis index was lower (P < 0.05) in the HCT treatment than in that of the HC treatment. Compared with the HC treatment, permeability and the electrophysiology parameter short circuit current for ruminal epithelial tissue were significantly decreased (P < 0.05) in the HCT treatment. The immunohistochemical results showed that the expression distribution of tight junctions including claudin-1, claudin-4, occludin, and zonula occludin-1 (ZO-1) was greater (P < 0.05) in the HCT treatments than in the HC treatment. The mRNA expression in the rumen epithelium of ZO-1, occludin, claudin-1, B-cell lymphoma/leukemia 2, nuclear factor erythroid-2 related factor 2 (Nrf2), superoxide dismutase 2 (SOD2), glutathione peroxidase 1, and the phase II metabolizing enzymes quinone oxidoreductase and heme oxygenase in the HCT group was significantly increased in comparison with the HC diet treatment (P < 0.05), whereas the mRNA expression of caspase 3, caspase 8, caspase 9, bcl-2 associated X protein, lipopolysaccharide binding protein, toll-like receptor 4, nuclear factor kappa-B (NFκB), tumor necrosis factor alpha, interleukin-1β, interleukin, and tumor necrosis factor receptor-associated factor 6 decreased significantly in the HCT treatment (P < 0.05). Compared with the HC treatment, the HCT diet significantly increased the protein expression of ZO-1, occludin, claudin-1, NQO1, HO-1, SOD2, serine/threonine kinase, p-Akt, Nrf2, and p-Nrf2; conversely, the expression of NFκB-related proteins p65 and pp65 was significantly decreased (P < 0.05). In addition, thiamine relieved the damage on the ruminal epithelium caused by the HC diet. The results show that dietary thiamine supplementation improves the rumen epithelial barrier function by regulating Nrf2–NFκB signaling pathways during high-concentrate-diet feeding.